An experimental study of corporate social responsibility through charitable giving in Bertrand markets - Feicht, Robert; Grimm, Veronika; Seebauer, Michael (Journal of Economic Behavior & Organization, 2016)
We experimentally investigate a Bertrand market with homogenous goods in which sellers can announce the donation of a share of their profits to an existing non-profit organization. In a 2 × 2 design, we vary the credibility of announcements and the efficiency of the contributions to the public fund. We find that sellers’ donations are strictly positive independently of the credibility of the announcements, and their donations are higher if announcements are credible and efficiency is high. However, market outcomes in terms of prices and profits do not differ significantly in any treatment that allows for contributions to a public fund. Analysis of buyer decisions reveals that prices are the main driver of purchase decisions while higher donations only affect purchase decisions when they are credible and price differences are negligible. Our results indicate that under intense competition the possibility of attracting customers through corporate social responsibility activities is limited, although the constant positive level of contributions suggests that norms lead to a certain minimum level of corporate social responsibilit
Keywords: Corporate social responsibility; Competition; Charitable giving; Experiment